2006
DOI: 10.1074/jbc.m607011200
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific Phosphorylation Differentiates Active from Inactive Forms of the Human T-cell Leukemia Virus Type 1 Tax Oncoprotein

Abstract: The human T-cell leukemia virus type 1 oncoprotein Tax is a phosphoprotein with a predominately nuclear subcellular localization that accomplishes multiple functions via protein-protein interactions. It has been proposed that regulation of this protein's pleiotropic functions may be accomplished through phosphorylation of specific amino acid residues. We have conducted a phosphoryl mapping of mammalian-expressed Tax protein using a combination of affinity purification, liquid chromatography tandem mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…Pin1 recognizes phosphorylated proteins. Tax is a phosphoprotein, which is phosphorylated on serine residue(s) in both mouse and human cells (12,13,27). We wondered next whether Pin1 might interact with Tax.…”
Section: Resultsmentioning
confidence: 99%
“…Pin1 recognizes phosphorylated proteins. Tax is a phosphoprotein, which is phosphorylated on serine residue(s) in both mouse and human cells (12,13,27). We wondered next whether Pin1 might interact with Tax.…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Posttranslational modification of proteins regulates protein functions by modifying their subcellular localization, stability, and/or network of interaction. We and others have described different forms of Tax posttranslational modifications including phosphorylation, 12,13 acetylation, 14 ubiquitylation, and small ubiquitin-like modifier (SUMO)ylation, 15,16 all of which are implicated in Tax-mediated activation of gene expression. Indeed, we showed that Tax is differentially ubiquitylated by either K-48 ubiquitin chains leading to Tax degradation by the proteasome or by K-63 ubiquitin chains that mediates IKK recruitment to the centrosome and IKK activation.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction was determined via immunoprecipitation following cotransfection of plasmids expressing both Tax and Chk2 and by co-immunoprecipitation following immunoprecipitation of endogenous Chk2. In the studies described herein, we used affinity purification of S-Tax using a system we recently described (35). In this study, the affinity isolation of Tax protein from cells resulted in a multiprotein complex containing endogenous Chk2 as a component (Fig.…”
Section: Tax Expression Results In Binding To and Activation Of Endogmentioning
confidence: 99%